Genetically encoded Ca2+ indicators; expanded affinity range, color hue and compatibility with optogenetics - Nagai, Takeharu; Horikawa, Kazuki; Saito, Kenta; Matsuda, Tomoki (Frontiers in Molecular Neuroscience, 2014)
Fluorescent protein-based indicators are invaluable tools for functional imaging of living cells and organisms. Genetically encoded calcium indicators (GECIs) such as derivatives of yellow cameleons (YCs) and GCaMPs/pericams (Miyawaki et al., 1997; Nakai et al., 2001; Nagai et al., 2001) are a highly advanced class of indicators. Continued efforts for improvement of the performance of GECIs have resulted in brighter indicators with better photo-stability and expanded dynamic range, thus improving the sensitivity of detection. Fine-tuning of other properties, including Ca2+ affinity and Hill constant, have also contributed to increase the detectability of Ca2+ dynamics. Emerging optogenetic technology has forced the spectrally compatible GECI color variants. In this opinion, we highlight the recent development of GECIs including photo-switchable Ca2+ indicators and bioluminescence-based Ca2+ indicator, mainly invented in our group, focusing especially on the parameters determining their performance in order to provide a guideline for the selection of appropriate GECI for a given experiment.